Fenomena Fatherless Perspektif Al Qur’an (Analisis Wacana Para Nabi dalam Mendidik Anak) - Farba, Aidal Jinani; Syauqani, Syamsu; Ridho, Abdul Rasyid (Program Studi Pendidikan Masyarakat, 2026)
Abstract: The objectives of this research were to examine the fatherless p enomenon in the context of Muslim society, and to analyze the discourse of father’ roles in the Prophets’ stories in the Qur'an. This research used a qualitative approach in the form of library research with a thematic (maudhu‘i) interpretation method combined with discourse analysis. The primary data sources were from the Qur'an and classical and contemporary tafsir books, while the secondary sources were obtained from relevant books and scientific articles. The data analysis was conducted descriptively and analytically to understand the construction of discourse on fatherhood in the Qur'an and its relevance to current social realities. The results of this research showed that the fatherless phenomenon in Muslim societies appeared in three main forms, namely physical, emotional, and functional forms, which were influenced by factors such as divorce, economic pressure, patriarchal culture, and low levels of parenting literacy. The Qur'an, through the stories of Prophet Ibrahim, Prophet Ya'quband Prophet Nuh, described the role of the father as a spiritual leader, educator of faith, moral guide, emotional protector, and loving dialogical communicator. Abstrak: Penelitian ini bertujuan untuk mengkaji fenomena fatherless dalam konteks masyarakat Muslim, serta menganalisis wacana peran ayah dalam kisah para Nabi di dalam Al-Qur’an. Penelitian ini menggunakan pendekatan kualitatif kepustakaan (library research) dengan metode Tafsīr tematik (maudhu‘i) yang dipadukan dengan analisis wacana. Sumber data primer berasal dari al-Qur’an dan kitab-kitab Tafsīr klasik maupun kontemporer, sedangkan sumber sekunder diperoleh dari buku serta artikel ilmiah yang relevan. Analisis data dilakukan secara deskriptif-analitis untuk memahami konstruksi wacana pengasuhan ayah dalam al-Qur’an dan relevansinya dengan realitas sosial saat ini. Hasil penelitian menunjukkan bahwa fenomena fatherless dalam masyarakat Muslim muncul dalam tiga bentuk utama, yaitu fatherless fisik, emosional, dan fungsional, yang dipengaruhi oleh faktor perceraian, tekanan ekonomi, budaya patriarki, serta rendahnya literasi parenting ayah. Al-Qur’an melalui kisah Nabi Ibrahim, Nabi Ya‘qub dan Nabi Nūḥ menggambarkan peran ayah sebagai pemimpin spiritual, pendidik iman, pembimbing moral, pelindung emosional, dan komunikator dialogis yang penuh kasih sayang.